Motive of Millennial Generation Competency in Public Service Implementation in Sidoarjo District - Moch Ali Mashuri (Journal of Economics, Business, and Government Challenges, 2019)
In the organization of the One-Stop Investment and Integrated Services Office of Sidoarjo Regency where there is a cultural clash in the organization, the baby boomer generation has a more rigid behavior in bureaucratic activities and is not following the development of ICT. The millennial generation is very flexible with ICT, is fast paced and wants ease in working in organizations, is bored with routine, and prefers to work behind the scenes. The purpose of this research is to uncover the motive of millennial generation competence in the implementation of electronic-based public services. The research method used is qualitative. Informants are employees of the One Stop Investment and Integrated Services Office of Sidoarjo Regency who fall into the millennial generation category of 8 informants. The results of this study that the motive for developing millennial generation competence in the implementation of electronic-based public services is obtained by millennial generation employees in addition to working to meet their basic daily needs, they want to work according to the rules (standard operational procedures) and the applicable system, achievement motives or rewards, and want to develop soft competence and hard competence to be more professional at work